The design and optimisation of cold asphalt emulsion mixtures - Ojum, Chibuzor Kingsley (2015)
Road structures are important to the survival of nations. As the cost for the rehabilitation and maintenance of highways soars, civil engineers and administrators face the ever present difficulty of meeting current resurfacing and rehabilitation needs. The deterioration of road structures under growing traffic weight and volume is occurring faster than agencies envisaged coupled with increasingly scarce and expensive new materials required. It is now apparent that for planning, design and construction for road structures, the most efficient and cost effective processes, materials and practices available must be appropriately considered.